Is improvement in the quality of life after subthalamic nucleus stimulation in Parkinson's disease predictable? - Daniels, Christine; Krack, Paul; Volkmann, Jens; Raethjen, Jan; Pinsker, Markus O.; Kloss, Manja; Tronnier, Volker; Schnitzler, Alfons; Wojtecki, Lars; Bötzel, Kai; Danek, Adrian; Hilker, Rüdiger; et al. (Movement disorders, 2011)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) significantly improves quality of life (QoL) in PD. However, QoL fails to improve in a relevant proportion of patients. We studied clinical baseline and progression parameters associated with improvement in QoL after DBS. Data from a German randomized, controlled study comparing DBS (60 patients) with best medical treatment (59 patients) were analyzed. Changes in patients' QoL were assessed using the Parkinson's Disease Questionnaire (PDQ-39) at baseline and at the 6-month follow-up. For the STN-DBS patients, the changes in PDQ-39 were correlated with predefined clinical preoperative and progression parameters. Scores for QoL improved after STN-DBS for 57% of the patients, and for 43% patients, they did not improve. Patients with improvement in QoL showed significantly higher cumulative daily “off” time. Changes in the PDQ-39 showed a significant positive correlation with the cumulative daily off time at baseline. Logistic regression analysis revealed that 1 additional hour off time at baseline increases the odds for improvement on PDQ-39 by a factor of 1.33 (odds ratio). In the postoperative course, changes in the PDQ-39 significantly correlated with the reduction of cumulative daily off time, an improvement on the UPDRS (UPDRS III off), and positive mood changes. Among the baseline parameters, the cumulative daily off time is the strongest predictor for improvement in disease-related QoL after DBS. Improvement in QoL after STN-DBS is also correlated with changes in motor functions and changes in depression and anxiety. © 2011 Movement Disorder Society